A guest from the past: A new genus and a new species of Deraeocorinae (Hemiptera: Heteroptera: Miridae) in Miocene Dominican amber - Kim, Junggon; Taszakowski, Artur; Herczek, Aleksander; Kim, Kwang-Ho; Jung, Sunghoon (Zootaxa, 2020)
The second fossil record of deraeocorine species from Miocene Dominican amber is presented with description of a new taxon, Amberderaeous gigophthalmus gen. and sp. nov. based on a well-preserved specimen. The need for revision of related group Eustictus and a comprehensive study of its tribal placement within Deraeocorinae are discussed.